ICT- social entrepreneurship nexus and job creation in Nigeria - Haoma Worgwu; Romanus Osabohien; Mamdouh Abdulaziz Saleh Al-Faryan; Ohalete I. Precious (International Journal of Management, Economics and Social Sciences (IJMESS), 2023)
This study examined the impact of social entrepreneurship and Information Communication Technology (ICT) utilization on employment in Nigeria. The study made use of survey data obtained from youth entrepreneurship with innovation (YouWiN) (2019). The study engaged descriptive statistics, the ordinary least squares (OLS) and propensity score matching (PSM) to achieve its objectives. The descriptive statistics show that there is a low proportion of social entrepreneurship. The result shows that social entrepreneurship contributes about 21% to employment. In addition, firm ICT utilizations; access to the internet and communication with clients via email contribute about 66% and 64% to firms' ability to contribute to employment level. The study concludes that policies and programmes to support social enterprises for employment creation should be implemented and properly executed.
Keywords: L26; M51; 330; Future employment; ICT adoption; entrepreneurship; sustainable development; Nigeria